2006
DOI: 10.4314/sajas.v36i1.3979
|View full text |Cite
|
Sign up to set email alerts
|

Effect of storage temperature on the quality of eggs from conjugated linoleic acid-fed laying hens

Abstract: This study was designed to investigate the effects of storage temperature on the quality of eggs from conjugated linoleic acid (CLA)-fed laying hens. For 40 days laying hens (20 per group) were fed a diet containing either 0.5% maize oil (Group A, Control) or 0.5% CLA (Group B). For fatty acid analysis, three eggs were collected after the eighth day of feeding. After two days of feeding, eggs were collected and stored for 28 days at 4 ºC, 15 ºC or 24 ºC for colour quality assessment. For pH measurements, 30 eg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…In the present study, while initially the yolk score was lower (paler), but not different in the LFE group comparable with the HFE group, following storage of eggs to 28 d the LFE group had a decreased yolk color score when compared with the HFE group. During storage, the vitelline membrane of yolk is weakened and becomes permeable to minerals and water migrating from albumen into the yolk, which could contribute to the discoloration of yolk (Aydin, 2006). Other research has reported that yolk pigments are closely associated with the lipid molecules of the yolk membranes; therefore as antioxidant protection diminishes during storage, reactive oxygen species (ROS) can cause oxidative degradation of yolk lipids (Bottje et al, 2006) and its pigments (Martino et al, 2014), which could have significant effect on yolk discoloration.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, while initially the yolk score was lower (paler), but not different in the LFE group comparable with the HFE group, following storage of eggs to 28 d the LFE group had a decreased yolk color score when compared with the HFE group. During storage, the vitelline membrane of yolk is weakened and becomes permeable to minerals and water migrating from albumen into the yolk, which could contribute to the discoloration of yolk (Aydin, 2006). Other research has reported that yolk pigments are closely associated with the lipid molecules of the yolk membranes; therefore as antioxidant protection diminishes during storage, reactive oxygen species (ROS) can cause oxidative degradation of yolk lipids (Bottje et al, 2006) and its pigments (Martino et al, 2014), which could have significant effect on yolk discoloration.…”
Section: Discussionmentioning
confidence: 99%
“…The studies conducted by Chamruspollert and Sell found that the addition of 5% CLA to the feed resulted in a reduction in the level of monounsaturated fatty acids compared to control eggs [46]. Other researchers such as Aydin [47,48] and Raes et al have reported similar observations [49]. Additionally, a decrease in the level of C17 and C18 (oleic acid) acids was detected.…”
Section: Methodsmentioning
confidence: 71%